Nature-Based Solutions for Co-mitigation of Air Pollution and Urban Heat in Indian Cities - Menon, Jyothi S.; Sharma, Richa (Frontiers in Sustainable Cities, 2021)
The urban population is subjected to multiple exposures of air pollution and heat stress and bear severe impacts on their health and wellbeing in terms of premature deaths and morbidity. India tops the list of countries with the highest air pollution exposure and hosts some of the most polluted cities in the world. Similarly, Indian cities are highly vulnerable to extreme heat with the frequency of heatwaves expected to increase several-fold in urban areas in India. It is reported that mitigating air pollution could reduce the rural-urban difference of the incoming radiation thus resulting in Urban Heat Island (UHI mitigation) in urban areas. Since the interaction between UHI and air pollution is dynamic and complex, both these factors should be considered by the urban authorities in designing mitigation strategies. Given the multi-functional nature and cost-effectiveness of Nature-Based Solutions (NBS), they appear to be the most appropriate remedy for environmental issues of urban areas, particularly in developing countries. In addition to improving public health (through reduction in air pollution and urban heat), NBS also provides a wide range of co-benefits such as reducing energy cost and health cost as well as conservation of biodiversity. This review is an attempt to understand the potential co-benefits of addressing air pollution and urban heat in a sustainable manner through NBS. A strategy for the successful implementation of NBS in Indian cities is also proposed based on the review that could help city planners and decision-makers in addressing these two issues in a comprehensive manner.